Development of Electrospun Polymer Nanofiber Membrane Based on PAN/PVDF as a Supercapacitor Separator - Nasikhudin Nasikhudin; Fina Nur Azizah; Markus Diantoro; Hartatiek Hartatiek; Ramesh T. Subramaniam; Ulwiyatus Sa’adah (Directorate for Research and Community Services, Institut Teknologi Bandung, 2023)
Among various types of energy storage, the supercapacitor is regarded as the most promising device due to its long cycling life, good cycling stability, and high power density. A supercapacitor is generally composed of electrodes, electrolytes, and a separator. The separator is one of the most important components, serving to prevent internal short circuits between the anode and the cathode. Herein, a nanostructured-based separator in a PAN/PVDF nanofiber scheme is introduced for improving the electrochemical performance of the supercapacitor. Briefly, the membranes were produced via the electrospinning technique. All of the raw materials were blended in various compositions of PVDF for optimization purposes. Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) were carried out to identify the microstructure of the nanofibers. The electrochemical properties of the membrane were measured using galvanostatic charge-discharge (GCD). Based on GCD, it was shown that the PAN/PVDF 20 wt% membrane exhibited the optimum gravimetric capacitance at 54.104 Fg-1 as evidenced by a high porosity percentage. Thus, the PAN/PVDF nanofiber has good potential as a separator for application in supercapacitors.